A female-biased expressed elongase involved in long-chain hydrocarbon biosynthesis and courtship behavior in Drosophila melanogaster. - Chertemps, T.; Duportets, L.; Labeur, C.; Ueda, R.; Takahashi, K.; Saigo, K.; Wicker-Thomas, C. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Drosophila melanogaster produces sexually dimorphic cuticular pheromones that are a key component of the courtship behavior leading to copulation. These molecules are hydrocarbons, with lengths of 23 and 25 carbons in males (mainly with one double bond) and 27 and 29 carbons in females (mainly with two double bonds). Here, we describe an elongase gene, eloF, with female-biased expression. The 771-bp ORF encodes a 257-aa protein that shows the highest sequence identity with mouse SSC1 elongase (33%). The activity of the cDNA expressed in yeast was elongation of saturated and unsaturated fatty acids up to C30. RNAi knockdown in Drosophila led to a dramatic modification of female hydrocarbons, with decreased C29 dienes and increased C25 dienes accompanied by a modification of several courtship parameters: an increase in copulation latency and a decrease in both copulation attempts and copulation. Feminization of the hydrocarbon profile in males by using targeted expression of the transformer gene resulted in high expression levels of eloF, suggesting that the gene is under the control of the sex-determination hierarchy. There is no expression of eloF in Drosophila simulans, which synthesize only C23 and C25 hydrocarbons. These results strongly support the hypothesis that eloF is a crucial enzyme for female pheromone biosynthesis and courtship behavior in D. melanogaster.